2011
DOI: 10.1016/j.ijlp.2011.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogy of individual choice and female inmate reentry in the U.S. Southwest

Abstract: Much of the mental health, substance use, and educational programming within a particular women’s prison in the southwestern United States promotes individual choice and agency. Incarcerated women from rural areas are told that their ability to succeed outside prison is primarily dependent upon their personal choices. Comparably little attention is given to preparing women for their upcoming release or to overcoming structural barriers that could undermine successful reentry within rural communities. As a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 42 publications
2
26
0
Order By: Relevance
“…24 In addition, moving away from the notion of individual responsibility and toward a more contextual approach is fitting. 25 Only if women's real obstacles are addressed at the community and policy level will their reentry have more than marginal success. For example, welfare and housing policies that exclude drug felons, the shortage of transitional housing, employment practices that discriminate against people with criminal justice records, and the patchwork of approaches to child welfare for incarcerated parents have to be revisited.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 In addition, moving away from the notion of individual responsibility and toward a more contextual approach is fitting. 25 Only if women's real obstacles are addressed at the community and policy level will their reentry have more than marginal success. For example, welfare and housing policies that exclude drug felons, the shortage of transitional housing, employment practices that discriminate against people with criminal justice records, and the patchwork of approaches to child welfare for incarcerated parents have to be revisited.…”
Section: Resultsmentioning
confidence: 99%
“…These studies also might test interventions that seek to connect people to health services, beyond those specific to chronic conditions. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research has concluded that addiction and problematic or abusive romantic relationships drive HIV risk behaviors among re-entering women (Staton-Tindall et al 2007) and that post-release substance use and mental health treatment are needed for sustained recovery from these conditions (Butzin et al 2005; Mallik-Kane and Vishner 2008; Martin et al 1995). However, publicly funded treatment is either not present or difficult to access in many communities, especially for women without childcare or reliable transportation (Johnson et al (in press; Kellett and Willging 2011; Ritchie 2001). Day-to-day survival (food, housing, a safe and legal way to make money) often takes precedence over treatment even for life-threatening medical conditions among re-entering populations (Johnson et al (2013), Johnson et al (in press; Stephenson et al 2005; Blank 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Day-to-day survival (food, housing, a safe and legal way to make money) often takes precedence over treatment even for life-threatening medical conditions among re-entering populations (Johnson et al (2013), Johnson et al (in press; Stephenson et al 2005; Blank 2013). Other research has noted that psychologically empowering women during incarceration does little in the long-term if women have little real power in the form of access to basic resources and safety in the communities to which they will return (Johnson et al (in press; Kellett and Willging 2011; Ritchie 2001). It is well-established that strengthening health and other resources for justice-involved individuals in the community provides better long-term health outcomes and is more cost-effective than investing in incarceration alone (Wolff 2005; McVay et al 2004; Natarajan et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, this advice fails to account for the environmental, economic and social context that have shaped these women’s lives and the world that they return to after prison release. For example, women face women significant structural and social barriers, such as poverty, discrimination, homelessness, histories of trauma and abuse, unemployment, limited education, limited treatment options, dependence on drug-using or abusive partner for shelter, economic support, or transportation to legally mandated treatment and other visits, and sometimes families and friendship networks in which there are no non-using members (Richie 2001; Kellett & Willging 2011; Johnson et al in press; Johnson in press). These factors limit women’s support network options after release (Kellett & Willging 2011).…”
Section: Introductionmentioning
confidence: 99%